Effects of NH4+, Na+, and Mg2+ ions on the corrosion behavior of galvanized steel in wet–dry cyclic conditions. Issue 8 (15th March 2021) - Neupane, Shova; Hastuty, Sri; Yadav, Neelima; Singh, Nilima; Gupta, Dipak K.; Yadav, Brahamdeo; Singh, Sanjay; Karki, Nabin; Kumari Das, Anju; Subedi, Vivek; Nakarmi, Krishna B.; Yadav, Amar P.
Abstract: The effect of cations on the corrosion of galvanized steel (GS) is scarcely reported. In this study, a wet–dry cyclic test was conducted to study NH4 +, Na +, and Mg 2+ cation effect on the corrosion behavior of GS available in Nepal. Fourteen wet–dry cycles (18 h wet and 6 h dry) were performed by exposing samples at 298 K with a relative humidity of 90% in a wet cycle and 50% in a dry cycle for 14 days. The cations strongly affect the corrosion rate of the GS sample estimated by weight loss and potentiodynamic polarization. The potentiodynamic polarization curves showed the inhibition of cathodic and anodic reactions by Mg 2+ ion, while the NH4 + ion only changed the cathodic reaction. Mg 2+ ion was found to shift the corrosion potential to noble values compared with NH4 + and Na + ions. A compact and thin corrosion products layer was developed in Mg 2+ salt solution in contrast to a thick and porous corrosion products layer in NH4 + and Na + salt solutions. Red rust due to corrosion of underlying steel appeared in the presence of NH4 + and Na + salt solutions. Finally, the weight loss data revealed that the corrosivity of cations for GS decreased in the order Na +  > NH4 +  > Mg 2+ . Abstract : In this study, a wet–dry cyclic test was conducted to study NH4 +, Na +, and Mg 2+ cations effect on the corrosion behavior of galvanized steel (GS) available in Nepal. The cations strongly affect the corrosion rate of the GS sample estimated by weight loss and potentiodynamic polarization. Mg 2+ ion was found to shift the corrosion potential to noble values compared with NH4 + and Na + ions.